Nurses’ Preparation to Manage Psychological Crises: The Importance of Psychological First Aid Training - Zahra Saboohi; Mahnaz Solhi (Journal of Client-centered Nursing Care, 2025)
Background: Crises and disasters, both natural and human-made, profoundly impact individuals and communities, leading to issues like anxiety, depression, and post-traumatic stress disorder (PTSD). Nurses, as first responders, play a crucial role in providing psychological first aid (PFA) to the affected persons. Main Idea: This commentary underscores the importance of PFA training to empower nurses in the effective management of psychological crisis. It also discusses strategies to enhance PFA training, including specialized education, team-based approaches, and access to supportive resources. Conclusion: PFA training enables nurses to offer effective support during crises and promoting community resilience. It is recommended that PFA be integrated into nursing education and professional development to strengthen nurses’ crisis response capabilities.